The Digital Divide in Post-Pandemic Education: Perceptions of Urban and Rural EFL Teachers in Indonesia - Sood, Muhammad; Nizarrahmadi, Nizarrahmadi; Yassin, Muhammad; Septiana, Dita (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
The COVID-19 pandemic acted as an unprecedented catalyst, forcing a global transition to online education and exposing deep-seated infrastructural and pedagogical vulnerabilities. This study investigates the lasting perceptions of this shift among English as a Foreign Language (EFL) teachers in Indonesia, focusing on the persistent challenge of the urban-rural digital divide. Employing a qualitative case study approach, this research explores the experiences of four junior high school English teachers in Pontianak Regency—two from urban and two from rural schools. Data were gathered through semi-structured interviews and document analysis. The findings reveal a significant dichotomy in teacher perceptions shaped by geographical location. Urban teachers, while initially optimistic, developed negative perceptions due to pedagogical frustrations and declining student engagement. In contrast, rural teachers held overwhelmingly negative perceptions from the start, citing insurmountable barriers related to internet access, device availability, and lack of digital literacy. The study concludes that the emergency remote teaching experience has solidified teacher perceptions that a one-size-fits-all approach to educational technology is untenable in a diverse landscape like Indonesia, highlighting an urgent need for context-aware policies and equitable infrastructure development in the post-pandemic era.